Hybrid electrolytic capacitor and method for manufacturing the same
By forming a dense organic conductive layer on the surface of the valve metal foil of the cathode and providing a conductive polymer layer with low impregnation of the electrolyte on the inorganic conductive layer, the static electricity of the existing hybrid electrolytic capacitor in the high frequency region is solved. The problems of low capacitance and high ESR achieve high electrostatic capacitance, low ESR and excellent high frequency characteristics and high temperature durability.
Patent Information
- Application Number
- CN202080087836.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-17
- Filing Date
- 2020-12-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-12-15
AI Technical Summary
The existing hybrid electrolytic capacitors have lower electrostatic capacitance in high-frequency regions (such as 20kHz), higher equivalent series resistance (ESR), and significantly higher ESR after high-temperature load test, making it difficult to meet high-static capacitance and low ESR. , excellent high frequency characteristics and high high temperature durability requirements.
A dense organic conductive layer containing conductive polymer is formed on the surface of the valve metal foil of the cathode, and a conductive polymer layer with low impregnation of the electrolyte is provided on the inorganic conductive layer to broaden the cathode oxidation film resistance is significantly greater than the interface. Area of resistance to high frequency area.
High electrostatic capacitance and low ESR in high-frequency regions (such as 20kHz), and low ESR is maintained before and after high-temperature load tests, meeting the requirements of high-frequency characteristics and high-temperature durability.
Smart Images

Figure CN114868217B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a hybrid electrolytic capacitor having a composite electrolyte layer and a method for manufacturing the same. The composite electrolyte layer comprises a solid electrolyte layer containing a conductive polymer and an electrolyte solution impregnated in gaps in the solid electrolyte layer. Background Art
[0002] As electronic devices become smaller and faster, capacitors used in power circuits and the like are increasingly required to have high electrostatic capacitance, low equivalent series resistance (hereinafter referred to as "ESR"), excellent high-frequency characteristics, and high high-temperature durability. In an electrolytic capacitor having an anode, an electrolyte, and a cathode, a solid electrolytic capacitor using a conductive polymer having high conductivity and high thermal decomposition temperature derived from a monomer having a π-conjugated double bond such as substituted or unsubstituted thiophene, pyrrole, aniline, etc. as an electrolyte is a capacitor suitable for responding to the above requirements, wherein the anode is provided with an oxide film as a dielectric on the surface of a substrate formed of a valve metal such as aluminum, tantalum, niobium, etc. and subjected to a surface expansion treatment, the electrolyte contacts the oxide film and acts as a true cathode, and the cathode (apparent cathode) contacts the electrolyte and is formed of a valve metal. However, the above solid electrolytic capacitor has the following problem, that is, there is a lack of repairing action on the defective part of the oxide film as a dielectric, and the leakage current slowly increases. Therefore, in order to solve this problem, a so-called hybrid electrolytic capacitor has been proposed in which an electrolyte having excellent oxide film repairing effect is impregnated into the gaps of the solid electrolyte layer. Hereinafter, an electrolytic capacitor having an electrolyte layer formed only of a conductive polymer is referred to as a "solid electrolytic capacitor", and an electrolytic capacitor having a composite electrolyte layer having a solid electrolyte layer containing a conductive polymer and an electrolyte impregnated into the gaps of the solid electrolyte layer is referred to as a "hybrid electrolytic capacitor".
[0003] For example, Patent Document 1 (Japanese Patent Publication No. 11-186110) discloses a hybrid electrolytic capacitor obtained by forming a conductive polymer layer in a capacitor element formed by winding an anode foil and an opposing cathode foil with a separator, and then impregnating an electrolyte solution. In this document, the conductive polymer layer is formed by chemical polymerization. In addition, it is shown that the leakage current of the hybrid electrolytic capacitor is significantly reduced before and after a high-temperature load test at 105°C and 1000 hours compared with the leakage current of a solid electrolytic capacitor having an electrolyte layer formed only of a conductive polymer. In addition, Patent Document 2 (Japanese Patent Publication No. 2008-010657) discloses a hybrid electrolytic capacitor obtained by impregnating a capacitor element formed by winding an anode foil and an opposing cathode foil with a dielectric oxide film through a separator, and then drying the capacitor element to form a conductive polymer layer, and then impregnating the gaps in the conductive polymer layer with an electrolyte. It is also shown that the leakage current of the hybrid electrolytic capacitor is much smaller than the leakage current of the hybrid electrolytic capacitor in which the conductive polymer layer is formed by chemical polymerization. The reason for this is that it is not the conductive polymer but the electrolyte that enters the defective part of the dielectric oxide film, so the repairing effect of the dielectric oxide film becomes higher. In the hybrid electrolytic capacitor disclosed in this document, the electrostatic capacitance at a frequency of 120 Hz increases due to the infiltration of conductive polymer particles into the etched pores of the anode, and the ESR at a frequency of 100 kHz decreases due to the infiltration of the electrolyte.
[0004] However, on the surface of the cathode formed of valve metal in a solid electrolytic capacitor, there is generally a natural oxide film even if no treatment is performed to form an oxide film. Therefore, the electrostatic capacitance (C) of a solid electrolytic capacitor is as shown in the following formula (1), which is the combined capacitance of the anode capacitance (Ca) and the cathode capacitance (Cc). Even if the anode capacitance is increased by etching, as long as the cathode has capacitance, the capacitance of the capacitor will be smaller than the anode capacitance.
[0005] [Mathematical formula 1]
[0006]
[0007] Therefore, in order to increase the cathode capacitance of the solid electrolytic capacitor, an etching process is performed on the valve metal foil of the cathode. However, if the etching is too large, the surface dissolution of the valve metal foil will be promoted at the same time, which will hinder the increase of the surface expansion rate, and it is easy to form an oxide film on the surface of the valve metal foil. Therefore, there is a limit in the increase of the cathode capacitance based on the etching process and the maintenance of the cathode capacitance. Therefore, a method is proposed to increase the cathode capacitance and inhibit the growth of the oxide film by forming a film of a conductive material that is not easy to form an oxide film on the surface of the valve metal foil of the cathode.
[0008] For example, Patent Document 3 (Japanese Patent Publication No. 2000-114109) discloses a solid electrolytic capacitor having a cathode foil obtained as follows, wherein a chemical oxide film is formed on the surface of a valve metal foil subjected to an etching process, and then a film formed of a metal nitride such as TiN, ZrN, TaN, etc., which is not easy to form an oxide film, is formed thereon by a vapor deposition method. According to the description, since a part of the chemical oxide film is removed by vapor deposition of the metal nitride and the metal nitride is connected to the valve metal foil, the cathode capacitance becomes infinite, and the capacitance (C) of the capacitor shown in the above formula is equal to the anode capacitance (Ca) and reaches the maximum. In addition, solid electrolytic capacitors are also known that use other materials instead of metal nitride films to achieve the same effect. For example, Patent Document 4 (Japanese Patent Publication No. 2005-109270) discloses a solid electrolytic capacitor having a cathode foil formed with a film of a metal carbide with low specific resistance such as TiC, WC, or ZrC by a vapor deposition method. Patent Document 5 (Japanese Patent Publication No. 2006-190878) discloses a solid electrolytic capacitor having a cathode formed with a carbon film by a dry plating method such as an ion plating method on the surface of a valve metal. Patent Document 6 (Japanese Patent Publication No. 2007-095865) discloses a cathode foil formed with a carbon film by a coating method.
[0009] In addition, in a hybrid electrolytic capacitor, since the electrostatic capacitance (C) of the capacitor is also the composite capacitance of the anode capacitance (Ca) and the cathode capacitance (Cc) as shown in the above formula (1), it has been proposed to use the methods shown in patent documents 3 to 6 to make the cathode capacitance close to infinity and make the capacitance (C) of the capacitor shown in the above formula close to the anode capacitance (Ca). For example, patent document 7 (WO2016 / 174806A1) discloses a hybrid electrolytic capacitor having a cathode foil as shown below, in which an inorganic conductive layer containing inorganic conductive materials such as carbon, nickel, nickel nitride, nickel carbide, titanium, titanium nitride, and titanium carbide is formed by evaporation and coating. In this document, as a problem point, if a polymer solution containing a raw material of a conductive polymer is used to form a solid electrolyte layer between the anode foil and the cathode foil, the film of the conductive polymer is too dense, so the electrolyte is not easy to spread over the surface of the anode foil, and the repairability of the defective dielectric layer is poor. Therefore, a dispersion in which particles of the conductive polymer are dispersed in a dispersion medium or a solution in which the conductive polymer is dissolved in a solvent is used to form the solid electrolyte layer. In addition, as a problem point, although the obtained solid electrolyte layer is uniform and has high flexibility, and the retention of the electrolyte is excellent, the solid electrolyte layer has low adhesion to the anode foil and the cathode foil. In particular, when an electrolyte is used, the electrolyte penetrates between the above-mentioned inorganic conductive layer and the solid electrolyte layer and is easy to hinder contact, so it is difficult to achieve high capacitance and low ESR of the capacitor. Therefore, the inorganic conductive layer is formed after the surface of the above-mentioned cathode foil is roughened by etching, etc., thereby improving the adhesion between the solid electrolyte layer and the inorganic conductive layer. In addition, there is a report that the electrostatic capacitance at a frequency of 120 Hz and the ESR at a frequency of 100 kHz of the obtained hybrid electrolytic capacitor were measured, and the capacitor achieved high capacitance and low ESR.
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: Japanese Patent Application Laid-Open No. 11-186110
[0013] Patent Document 2: Japanese Patent Application Publication No. 2008-010657
[0014] Patent Document 3: Japanese Patent Application Publication No. 2000-114109
[0015] Patent Document 4: Japanese Patent Application Publication No. 2007-095865
[0016] Patent Document 5: Japanese Patent Application Publication No. 2006-190878
[0017] Patent Document 6: Japanese Patent Application Publication No. 2007-095865
[0018] Patent Document 7: WO2016 / 174806A1 Summary of the invention
[0019] Problems to be solved by the invention
[0020] According to the hybrid electrolytic capacitor, the problem of increased leakage current of the solid electrolytic capacitor can be solved. In addition, by providing an inorganic conductive layer on the cathode of the capacitor, high capacitance can be achieved. The evaluation of the electrostatic capacitance of the hybrid electrolytic capacitor so far is generally carried out only under the condition of a frequency of 120Hz as shown in Patent Documents 2 and 7, and the evaluation in the high frequency region is insufficient. Therefore, the inventors and others measured the electrostatic capacitance at 20kHz for a hybrid electrolytic capacitor having the same structure as the capacitor of Patent Document 7, that is, a hybrid electrolytic capacitor having a cathode with a titanium carbide film or a carbon vapor-deposited film as an inorganic conductive layer on a valve metal foil subjected to etching. As a result, it was found that any capacitor showed a low capacitance and should be improved. In addition, the ESR of the above-mentioned hybrid electrolytic capacitor was measured under the conditions of frequencies of 20kHz and 100kHz. As a result, it was found that any capacitor showed a high ESR value, and a significant increase in ESR was observed after a high-temperature endurance test, which should still be improved. On the other hand, as described above, hybrid electrolytic capacitors are also increasingly required to have high electrostatic capacitance, low ESR, excellent high-frequency characteristics, and high high-temperature durability.
[0021] Therefore, an object of the present invention is to provide a hybrid electrolytic capacitor that can meet the above-mentioned requirements.
[0022] Means for solving problems
[0023] The hybrid electrolytic capacitor of the prior art having a cathode with an inorganic conductive layer on a valve metal foil can achieve a high capacitance at a frequency of 120 Hz, but cannot achieve a high capacitance at a frequency of 20 kHz. Figure 2 and Figure 3 The reason is explained. Figure 2 is a diagram for explaining the resistance component and the capacitance component of the cathode and the vicinity of the cathode of a hybrid electrolytic capacitor having the same structure as that of the prior art document, Figure 3 The figure is a diagram for explaining the equivalent circuit structure of the hybrid electrolytic capacitor in the low frequency region and the high frequency region. The electrostatic capacitance of the capacitor represented by C in the above formula (1) is Figure 3 The symbol Cap is used to indicate that the electrostatic capacitance of the anode represented by Ca in the above formula (1) is Figure 3 Using C AOXThe symbol indicates that the electrostatic capacitance of the anode represented by Cc in the above formula (1) is Figure 3 Using C COX The symbol indicates .
[0024] like Figure 2 As shown in the figure, the cathode of the hybrid electrolytic capacitor and the circuit structure near the cathode can be used to make use of the parallel interface resistance R IN , cathode oxide film resistance R COX And cathode oxide film capacitor C COX In addition, in the low frequency f region, the cathode oxide film resistance R COx Significantly larger than the interface resistance R IN , so the equivalent circuit of the hybrid electrolytic capacitor can be simplified as follows Figure 3 As shown in the left figure of . As a result, the electrostatic capacitance Cap of the capacitor is roughly equal to the capacitance C of the anodic oxide film. AOX , as shown in the existing literature, to achieve high capacitance. However, in the high frequency f region, R IN Greater than 1 / (ωC COx ), C appears COx , the equivalent circuit of the hybrid electrolytic capacitor is as follows Figure 3 As a result, the electrostatic capacitance Cap of the capacitor is the anodic oxide film capacitance C AOX C cOx The combined capacitance is less than the anodized film capacitance C AOX .
[0025] Therefore, the inventors proposed to reduce the interface resistance R IN In other words, as a method to obtain the same Figure 3 The equivalent circuit shown in the left figure of the present invention was used to study the method of providing a conductive polymer layer with low electrolyte permeability on the inorganic conductive layer of the cathode, which had not been used in previous hybrid electrolytic capacitors. It was then confirmed that the cathode oxide film resistance R COX Significantly greater than the interface resistance R IN The present invention was completed by expanding the range of the inorganic conductive layer to the high frequency range, and realizing high capacitance in the high frequency range. In addition, it was confirmed that the obtained capacitor showed low ESR before and after the high temperature load test, thereby completing the present invention. It was also found that the above-mentioned effects can be obtained independently of the presence or absence of etching and the type of inorganic conductive layer.
[0026] Therefore, the present invention firstly relates to a hybrid electrolytic capacitor, characterized by comprising:
[0027] A cathode having a cathode substrate formed of a valve metal, an oxide layer formed of an oxide of the valve metal provided on the surface of the cathode substrate, an inorganic conductive layer comprising an inorganic conductive material provided on the surface of the oxide layer, and an organic conductive layer comprising a conductive polymer provided on the surface of the inorganic conductive layer;
[0028] An anode having an anode substrate formed of a valve metal and a dielectric layer formed of an oxide of the valve metal constituting the anode substrate and provided on a surface of the anode substrate; and
[0029] The composite electrolyte layer comprises a solid electrolyte layer containing conductive polymer particles provided between and in contact with the organic conductive layer of the cathode and the dielectric layer of the anode, and an electrolyte solution filled between the conductive polymer particles of the solid electrolyte layer.
[0030] In the present invention, the cathode substrate may or may not have etch pits. When etch pits are present, they may be tunnel pits, sponge pits, through-type pits, or residual core pits. In addition, the oxide layer provided on the surface of the cathode substrate may be a chemically formed oxide film or a natural oxide film.
[0031] The present invention is characterized in that an organic conductive layer containing a conductive polymer is provided on the cathode. The organic conductive layer is preferably dense, and specifically preferably has a density of 1.15 to 1.80 g / cm 3 The density is preferably in the range of 1.20 to 1.80 g / cm 3 The density is preferably in the range of 1.60 to 1.80 g / cm 3 By making the above-mentioned dense organic conductive layer contact with the composite electrolyte layer, high electrostatic capacitance, low ESR, excellent high-frequency characteristics and high high-temperature durability of the hybrid electrolytic capacitor can be appropriately provided. If the density of the organic conductive layer of the cathode is less than 1.15 g / cm 3 , it is difficult to obtain the effect of the present invention, and it is difficult to manufacture a density greater than 1.80 g / cm 3 The density of the dense organic conductive layer is higher than that of the solid electrolyte layer in a state of retaining the electrolyte solution, so most of the electrolyte solution in the composite electrolyte layer is retained by the solid electrolyte layer.
[0032] By using the electrolytic polymerization of the constituent elements formed by the cathode substrate, the oxide layer and the inorganic conductive layer as the working electrode, the organic conductive layer of the cathode can be formed on the inorganic conductive layer with good adhesion. Therefore, in a suitable embodiment of the present invention, the organic conductive layer is an electrolytic polymerization film. It should be noted that in this specification, the constituent elements formed by the cathode substrate, the oxide layer and the inorganic conductive layer are sometimes expressed as "supports", and the constituent elements formed by the cathode substrate and the oxide layer are expressed as "collectors".
[0033] On the other hand, the composite electrolyte layer can be obtained by the same method as in the past, that is, by filling a dispersion containing conductive polymer particles and a dispersion medium between the dielectric layer of the anode and the organic conductive layer of the cathode and drying the dispersion to form a solid electrolyte layer, and then impregnating the solid electrolyte layer with an electrolyte.
[0034] Therefore, the present invention also relates to a method for manufacturing a hybrid electrolytic capacitor, characterized in that:
[0035] include:
[0036] A cathode forming step, comprising: forming an inorganic conductive layer using an inorganic conductive material on the surface of an oxide layer formed of an oxide of the valve metal provided on the surface of a cathode substrate formed of the valve metal, and forming an organic conductive layer including a conductive polymer on the surface of the inorganic conductive layer by electrolytic polymerization of a monomer having a π-conjugated double bond;
[0037] an anode forming step of forming a dielectric layer by oxidizing a surface of an anode substrate formed of a valve metal; and
[0038] The composite electrolyte layer forming step includes: a step of forming a solid electrolyte layer by filling a dispersion containing particles of a conductive polymer and a dispersion medium between the organic conductive layer of the cathode and the dielectric layer of the anode and drying the dispersion, and a step of impregnating the solid electrolyte layer with the electrolyte. Furthermore, by using an electrolytic polymerization solution containing a solvent formed by 100 to 80% by mass of water and 0 to 20% by mass of an organic solvent, a monomer having a π-conjugated double bond and a supporting electrolyte, a composite electrolyte layer having a density of 1.15 to 1.80 g / cm 3 A range of density of the organic conductive layer.
[0039] There is no particular limitation on the types of the conductive polymer in the organic conductive layer and the conductive polymer in the solid electrolyte layer, and conductive polymers derived from monomers having known π-conjugated double bonds can be used. The two may be polymers of the same type (polymers derived from the same monomer) or polymers of different types (polymers derived from different monomers), but if both are poly(3,4-ethylenedioxythiophene), particularly high conductivity and high temperature durability can be obtained, which is therefore preferred.
[0040] As described above, the effect of the present invention can be obtained independently of whether the cathode substrate is etched or not and the type of inorganic conductive layer. However, if the inorganic conductive material constituting the inorganic conductive layer is carbon, the change in electrostatic capacitance before and after the high-temperature load test is small both in the low-frequency region and in the high-frequency region, and therefore it is preferred.
[0041] In addition, in PCT / JP2019 / 022741, which was unpublished when the applicant filed the application that is considered as the basis for the priority claim of the present application, an electrode body used in the cathode of an electrolytic capacitor showing good capacitance was disclosed, characterized in that it has a cathode body formed of a valve-acting metal and having a surface expansion layer formed on the surface, and a carbon layer formed on the surface expansion layer, and the boundary between the surface expansion layer and the carbon layer has a concave-convex shape. In addition, as a method for manufacturing an electrode body with suitable performance, a method of applying a slurry containing carbon particles on the surface of the cathode body and applying a pressing treatment after drying was disclosed. If the method is implemented using an aluminum foil to which an etching treatment has been applied as a substrate, the carbon particles can be pressed into the etched pits of the aluminum foil by the pressing treatment, and the carbon particles can be made to pierce the oxide film on the aluminum foil, so that the carbon layer is conductive with the aluminum of the substrate.
[0042] In PCT / JP2019 / 022741, although the performance of a wet electrolytic capacitor using the above-mentioned electrode body as a cathode is described in detail, there is no description of the performance of the capacitor when the above-mentioned electrode body is applied to a hybrid electrolytic capacitor. The inventors used the above-mentioned electrode body with suitable performance as a support for an organic conductive layer for obtaining a cathode by electrolytic polymerization, and evaluated the performance of the resulting hybrid electrolytic capacitor. It was found that the change in electrostatic capacitance before and after the high-temperature load test was particularly small both in the low-frequency region and in the high-frequency region. Therefore, in a particularly preferred embodiment of the hybrid electrolytic capacitor of the present invention, the above-mentioned cathode substrate has an etch pit, and the above-mentioned inorganic conductive layer is a carbon coating layer containing carbon particles, and the carbon coating layer has an entry portion that enters the above-mentioned etch pit and a penetration portion that penetrates the above-mentioned oxide layer and is conductive with the above-mentioned cathode substrate.
[0043] Effects of the Invention
[0044] The hybrid electrolytic capacitor of the present invention exhibits high electrostatic capacitance, low ESR, excellent high-frequency characteristics, and high high-temperature durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 It is a schematic diagram schematically showing the structure of the hybrid electrolytic capacitor of the present invention.
[0046] Figure 2 This is a diagram for explaining the resistance component and the capacitance component of the cathode and the vicinity of the cathode of a hybrid electrolytic capacitor of the prior art.
[0047] Figure 3 It is a diagram for explaining the configuration of an equivalent circuit in a low-frequency region and a high-frequency region of a hybrid electrolytic capacitor of the related art. DETAILED DESCRIPTION
[0048] Figure 1 The structure of the hybrid electrolytic capacitor of the present invention is schematically shown in FIG. The hybrid electrolytic capacitor 1 comprises: a cathode 10 having a cathode substrate 11 formed of a valve metal, an oxide layer 12 formed of an oxide of the valve metal provided on the surface of the cathode substrate 11, an inorganic conductive layer 13 containing an inorganic conductive material provided on the surface of the oxide layer 12, and an organic conductive layer 14 containing a conductive polymer provided on the surface of the inorganic conductive layer 13; an anode 20 having an anode substrate 21 formed of a valve metal, and a dielectric layer 22 formed of an oxide of the valve metal constituting the anode substrate provided on the surface of the anode substrate 21; and a composite electrolyte layer 30 having a solid electrolyte layer 31 containing particles 31a of a conductive polymer provided between and in contact with the organic conductive layer 14 of the cathode 10 and the dielectric layer 22 of the anode 20, and an electrolyte solution 32 filled between the particles 31a of the conductive polymer in the solid electrolyte layer 31.
[0049] The organic conductive layer 14 of the cathode 10, which is made of a conductive polymer, is preferably dense, and specifically preferably has a density of 1.15 to 1.80 g / cm 3 The density is preferably in the range of 1.20 to 1.80 g / cm 3 The density is preferably in the range of 1.60 to 1.80 g / cm 3 By making the dense organic conductive layer 14 contact with the composite electrolyte layer 30, the hybrid electrolytic capacitor 1 can be appropriately provided with high electrostatic capacitance, low ESR, excellent high-frequency characteristics and high high-temperature durability. If the density of the organic conductive layer 14 of the cathode 10 is less than 1.15 g / cm 3 , it is difficult to obtain the effect of the present invention, and it is difficult to manufacture a density greater than 1.80 g / cm 3 conductive polymer layer.
[0050] The hybrid electrolytic capacitor of the present invention can be manufactured by a method including a cathode forming step, an anode forming step, and a composite electrolyte layer forming step as shown below. Each step will be described in detail below.
[0051] (1) Cathode Formation Process
[0052] The cathode forming process includes a stage of forming an inorganic conductive layer using an inorganic conductive material on the surface of an oxide layer formed by an oxide of the valve metal provided on the surface of a cathode substrate formed by the valve metal, and a stage of forming an organic conductive layer containing a conductive polymer on the surface of the inorganic conductive layer through electrolytic polymerization of a monomer having a π-conjugated double bond.
[0053] As the cathode substrate, a substrate formed of a valve metal used as a cathode substrate in a conventional hybrid electrolytic capacitor can be used without particular limitation. For example, a foil formed of a valve metal such as aluminum, tantalum, niobium, titanium, hafnium, zirconium, zinc, tungsten, bismuth and antimony can be used, and aluminum foil is particularly preferred. As the cathode substrate, these foils can be used in the form of so-called plain foils without being subjected to etching treatment, and foils whose surface area is increased by applying chemical or electrochemical etching treatment can be used. The etch pits in the cathode substrate can be tunnel pits, sponge pits, through-type pits, or residual core pits, which can be appropriately selected according to the purpose of the hybrid electrolytic capacitor. These etch pits can be formed using known AC electrolysis methods and DC electrolysis methods.
[0054] The oxide layer provided on the surface of the cathode substrate can be a natural oxide film that is usually present on the surface of the cathode substrate, or, on this basis, a chemical oxide film can be formed on the surface of the cathode substrate by chemical treatment using a chemical conversion liquid such as an aqueous solution of ammonium borate, an aqueous solution of ammonium adipate, or an aqueous solution of ammonium phosphate, and the chemical oxide film can be used as the oxide layer.
[0055] First, an inorganic conductive layer is formed on the surface of the above-mentioned oxide layer using an inorganic conductive material to obtain a support. The inorganic conductive layer can be 1 layer, or different inorganic conductive materials can be used to form more than 2 layers of inorganic conductive layers. As long as the type of inorganic conductive material forming the inorganic conductive layer and the formation method of the inorganic conductive layer can ensure sufficient adhesion with the cathode oxide layer and can form an organic conductive layer with good surface adhesion on the inorganic conductive layer in the following stage, there is no particular limitation. For example, inorganic conductive materials such as carbon, titanium, platinum, gold, silver, cobalt, nickel, and iron can be stacked on the oxide film using vacuum evaporation, sputtering, ion plating, coating, electroplating, and electroless plating to provide an inorganic conductive layer. If carbon is used as the inorganic conductive material, the change in electrostatic capacitance before and after the high temperature load test is less in the low frequency region or in the high frequency region, so it is preferred.
[0056] In a particularly suitable embodiment of the cathode, the cathode substrate has an etch pit, and the inorganic conductive layer is a carbon coating layer containing carbon particles, the carbon coating layer having an entry portion that enters the etch pit and a penetration portion that penetrates the oxide layer and is in electrical communication with the cathode substrate. The particularly suitable inorganic conductive layer can be formed by implementing the following stages, namely, a coating stage, in which a carbon slurry containing carbon particles is coated on the surface of the oxide layer and dried to form a slurry layer; and a pressing stage, in which a pressing treatment is applied to the slurry layer to press the carbon particles into the etch pit of the cathode substrate and cause the carbon particles to pierce the oxide layer.
[0057] The carbon slurry used in the coating stage contains at least carbon particles, a binder and a dispersion medium. As carbon particles, carbon particles with various shapes such as fibrous, spherical, and flaky can be used without particular limitation, and examples include porous carbon such as carbon nanotubes, carbon nanofibers, carbon nanohorns, activated carbon, carbon black such as Ketjen black, furnace black, channel black, and acetylene black, amorphous carbon, natural graphite, artificial graphite, graphitized Ketjen black, and mesoporous carbon. These carbon particles can be used alone or in combination of two or more. However, in the carbon slurry used to form a carbon coating layer having an entry portion into the etch pit, of course, at least carbon particles having a particle size that can enter the etch pit of the cathode substrate are included. In a suitable manner, carbon particles having a particle size that cannot enter the etch pit of the cathode substrate are also included in the carbon slurry. In this suitable manner, the carbon particles can be formed from the same type of carbon. In other words, the same type of carbon having a wide range of particle size distribution, such as acetylene black having a wide range of particle size distribution, can be used, or a mixture of different types of carbon, such as a mixture of flaky graphite and acetylene black can be used to obtain a wide range of particle size distribution of carbon particles.
[0058] As the binder, known binders such as polytetrafluoroethylene, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, polyvinyl fluoride, carboxymethyl cellulose, styrene butadiene rubber can be used alone or in combination of two or more. As the dispersion medium, dispersion mediums that do not adversely affect other constituent elements such as N-methylpyrrolidone, dimethylformamide, tetrahydrofuran, isopropyl alcohol, water, etc. can be used without particular limitation.
[0059] There is no particular limitation on the wet mixing method of carbon particles, binder and dispersion medium for obtaining carbon slurry, and the mixture can be performed by manual mixing using a mortar, or by using a known mixing device such as a stirrer or homogenizer. As long as a uniform carbon slurry can be obtained, there is no particular limitation on the mixing time.
[0060] The obtained carbon slurry is applied to the surface of the oxide layer provided on the surface of the cathode substrate by a known coating method such as a doctor blade method or a casting method under normal pressure or reduced pressure and dried to form a slurry layer. Then, a pressing step of applying pressure to the obtained slurry layer is performed.
[0061] Before the carbon slurry is applied, a base layer formed of a conductive inorganic material such as carbon, titanium nitride, or titanium carbide may be provided on the surface of the oxide layer by using a vapor deposition method such as vacuum vapor deposition or ion plating. The base layer formed by the vapor deposition method may be formed only on the surface of the oxide layer on the outer surface of the cathode substrate in the surface of the oxide layer, and not on the surface of the oxide layer on the surface of the etch pit.
[0062] The pressing stage can be performed by roller pressing or vertical pressing. It is necessary to apply pressure in such a way that the carbon particles are pressed into the etched pits of the cathode substrate and the carbon particles pierce the oxide layer. In the case where a base layer is provided on the outer surface of the cathode substrate, it is necessary to apply pressure in such a way that the carbon particles pierce the base layer and the oxide layer. It is preferred to adjust the pressure in the pressing stage so that the interface resistance of the support is 10 mΩcm. 2 Below, preferably 6 mΩcm 2 Below, more preferably 3mΩcm 2Hereinafter, it is preferred to adjust as follows, that is, to make the average value of the length of the entry portion of the carbon coating layer more than 1 / 5 of the average value of the length of the etch pit, preferably more than 1 / 4. Here, the so-called "interface resistance of the support body" refers to the interface resistance measured between the carbon coating layer and the cathode substrate, which depends on all interfaces contained in the support body, and can be obtained by a known measurement method, for example, it can be obtained by the following method. First, a support body having a carbon coating layer with a thickness of 20 to 30 μm is formed. Then, an arrangement of a plurality of measuring inspection needles for measuring the potential of the surface of the carbon coating layer at many positions, and an arrangement of probes composed of application inspection needles for applying current to the support body provided around the arrangement are brought into contact with the surface of the carbon coating layer, a prescribed direct current is applied between the application inspection needles, and the potential generated on the surface of the carbon coating layer when the current is applied is measured at many positions using the measuring inspection needles, thereby obtaining the measured value of the potential distribution. Then, a model formula is constructed in which the measured thickness of the collector, the resistance of the collector, and the thickness of the carbon coating layer are set as fixed values, and the resistance of the carbon coating layer and the interface resistance are set as variables, and the potential distribution of the model formula is calculated while changing the variables. Thereafter, the interface resistance when the calculated value of the potential distribution obtained by the model formula is consistent with the measured value of the potential distribution is the "interface resistance of the support". As an apparatus suitable for obtaining the interface resistance of the support, for example, the electrode resistance measurement system RM2610 manufactured by Hioki Electric Chemical Co., Ltd. can be cited. There is no particular limitation on the thickness of the carbon coating layer as long as the entire surface of the oxide layer and the cathode substrate to be covered by the carbon coating layer is covered, for example, it can be set to an average thickness of 0.5 to 30 μm. In the above-mentioned measurement method using the potential distribution, a carbon coating layer with a thickness of 20 to 30 μm is used, but the value of the interface resistance of the support obtained by pressing a thinner carbon coating layer with the same pressure is similar to the value of the interface resistance of the support having a carbon coating layer with a thickness of 20 to 30 μm.
[0063] If particles having a particle size that cannot enter the etch pits are included as carbon particles in the carbon coating layer, the particles substantially exist in the region of the carbon coating layer other than the entry portion. During the pressing stage, the particles serve to compress and deform the etch pits, thereby appropriately improving the adhesion between the carbon coating layer and the current collector contacting the carbon coating layer, and appropriately reducing the interfacial resistance between the carbon coating layer and the current collector. In addition, the particles serve to appropriately press carbon particles having a particle size that can enter the etch pits into the etch pits. On the other hand, carbon particles having a particle size that can enter the etch pits are not only filled in the entry portion of the carbon coating layer but also filled in the gaps between large carbon particles existing only in the region other than the entry portion, and thus exist throughout the carbon coating layer. Further, if the particles having a particle size that cannot enter the etch pits are formed of flaky graphite, the flaky graphite is liable to orient in such a manner that their basal planes (Japanese: ベーサル面) overlap each other to compress and deform the etch pits, and is liable to pierce the oxide layer to conduct with the cathode substrate. In addition, if flaky graphite and carbon black are used in combination, it is easy to press the carbon black into the etch pits and between the flaky graphite to form an inorganic conductive layer that is particularly dense, has excellent conductivity, and has excellent adhesion to the current collector.
[0064] Then, an organic conductive layer containing a conductive polymer is formed on the surface of the above inorganic conductive layer. Preferably, the organic conductive layer is dense. Specifically, it preferably has a density in the range of 1.15 to 1.80 g / cm 3 and more preferably has a density in the range of 1.20 to 1.80 g / cm 3 and particularly preferably has a density in the range of 1.60 to 1.80 g / cm 3 As long as a dense organic conductive layer having a density in this range can be formed, there is no particular limitation on the formation method thereof, and the dense organic conductive layer can be suitably obtained via electrolytic polymerization.
[0065] Into a polymerization solution containing at least a monomer, a supporting electrolyte, and a solvent, a support formed of a cathode substrate, an oxide layer, and an inorganic conductive layer is introduced as a working electrode, together with a counter electrode such as a platinum plate or a nickel plate, and a voltage is applied between the working electrode and the counter electrode to perform electrolytic polymerization. During the electrolytic polymerization, anions released from the supporting electrolyte are included in the conductive polymer layer as dopants.
[0066] As the solvent for the polymerization solution for electrolytic polymerization, a solvent that can dissolve a desired amount of the monomer and the supporting electrolyte and does not have an adverse effect on the electrolytic polymerization can be used. However, in order to obtain a dense organic conductive layer having a density in the range of 1.15 to 1.80 g / cm 3In order to prepare an organic conductive layer with a density in the range of , it is preferred to use a solvent formed by 100 to 80% by mass of water and 0 to 20% by mass of an organic solvent (hereinafter, a solvent formed by 100 to 80% by mass of water and 0 to 20% by mass of an organic solvent is referred to as a "water-rich solvent."). Examples of organic solvents that can be mixed with water include methanol, ethanol, isopropanol, butanol, ethylene glycol, acetonitrile, acetone, tetrahydrofuran, methyl acetate, and the like. The higher the water content in the solvent, the greater the density of the organic conductive layer. If only water is used as the solvent, a density of 1.60 to 1.80 g / cm 3 A density in the range of 200 to 400 is particularly preferred for the organic conductive layer.
[0067] As the monomer, any monomer having a π-conjugated double bond that has been used in the past to produce a conductive polymer can be used without particular limitation. Representative monomers are shown below. These monomers can be used alone or in the form of a mixture of two or more.
[0068] First, thiophene and thiophene derivatives can be mentioned, for example, 3-alkylthiophenes such as 3-methylthiophene and 3-ethylthiophene, 3,4-dialkylthiophenes such as 3,4-dimethylthiophene and 3,4-diethylthiophene, 3-alkoxythiophenes such as 3-methoxythiophene and 3-ethoxythiophene, 3,4-dialkoxythiophenes such as 3,4-dimethoxythiophene and 3,4-diethoxythiophene, 3,4-methylenedioxythiophene, 3,4-ethylenedioxythiophene, 3,4-(1,2-propylenedioxy)thiophene and the like, Thiophene, 3,4-methyleneoxythiothiophene, 3,4-ethyleneoxythiothiophene, 3,4-(1,2-propyleneoxythio)thiophene and the like 3,4-alkylenedithiothiophene, 3,4-methylenedithiothiophene, 3,4-ethylenedithiothiophene, 3,4-(1,2-propylenedithio)thiophene and the like alkylthiophene[3,4-b]thiophene, isopropylthiophene[3,4-b]thiophene, tert-butylthiophene[3,4-b]thiophene and the like alkylthiophene[3,4-b]thiophene.
[0069] In addition, pyrrole and pyrrole derivatives can be mentioned, for example, N-alkylpyrroles such as N-methylpyrrole and N-ethylpyrrole, 3-alkylpyrroles such as 3-methylpyrrole and 3-ethylpyrrole, 3-alkoxypyrroles such as 3-methoxypyrrole and 3-ethoxypyrrole, N-phenylpyrrole, N-naphthylpyrrole, 3,4-dialkylpyrroles such as 3,4-dimethylpyrrole and 3,4-diethylpyrrole, and 3,4-dialkoxypyrroles such as 3,4-dimethoxypyrrole and 3,4-diethoxypyrrole. In addition, aniline and aniline derivatives may be mentioned, for example, 2,5-dialkylanilines such as 2,5-dimethylaniline and 2-methyl-5-ethylaniline, 2,5-dialkoxyanilines such as 2,5-dimethoxyaniline and 2-methoxy-5-ethoxyaniline, 2,3,5-trimethoxyaniline, 2,3,5-trialkoxyanilines such as 2,3,5-triethoxyaniline, 2,3,5,6-tetramethoxyaniline, 2,3,5 , 2,3,5,6-tetraalkoxyanilines such as 6-tetraethoxyaniline, and furan and furan derivatives, for example, 3-alkylfurans such as 3-methylfuran and 3-ethylfuran, 3,4-dialkylfurans such as 3,4-dimethylfuran and 3,4-diethylfuran, 3-alkoxyfurans such as 3-methoxyfuran and 3-ethoxyfuran, and 3,4-dialkoxyfurans such as 3,4-dimethoxyfuran and 3,4-diethoxyfuran.
[0070] As the monomer, it is preferred to use a monomer selected from thiophenes having substituents at positions 3 and 4. The substituents at positions 3 and 4 of the thiophene ring can form a ring together with the carbon atoms at positions 3 and 4. In particular, 3,4-(ethylenedioxythiophene) is preferred because it can provide a conductive polymer having high conductivity and excellent heat resistance.
[0071] As supporting electrolyte, the compound of releasing dopant contained in the previous conductive polymer can be used without special limitation. For example, in addition to the inorganic acids such as boric acid, nitric acid, phosphoric acid, acetic acid, oxalic acid, citric acid, etc., sulfonic acids such as methanesulfonic acid, dodecylsulfonic acid, p-toluenesulfonic acid and their salts can also be illustrated. In addition, polycarboxylic acids such as polyacrylic acid, polymethacrylic acid, polymaleic acid, polysulfonic acids such as polystyrenesulfonic acid, polyvinylsulfonic acid, and their salts can also be used as supporting electrolytes. In addition, boron complexes such as boron disalicylic acid, boron dioxalic acid, boron dimalonic acid, sulfonyl imide and their salts can also be used as supporting electrolytes. As salts, alkali metal salts such as lithium salts, sodium salts, potassium salts, ammonium salts, ethylammonium salts, alkylammonium salts such as butylammonium salts can be illustrated. Among them, at least one compound having an anion molecular weight of 200 or more as an organic compound without a sulfonic acid group or a sulfonate group, particularly borodisalicylic acid or its salt, sulfonylimidic acid and its salt are preferred because they can provide a conductive polymer with excellent heat resistance. These supporting electrolytes can be used alone or in combination of two or more, depending on the type of supporting electrolyte, in an amount below the saturated solubility of the polymer solution and in a concentration sufficient to obtain an electric current for electrolytic polymerization.
[0072] In the polymerization solution for electrolytic polymerization, in addition to the monomer, supporting electrolyte and solvent as essential components, other components that do not adversely affect the electrolytic polymerization may be further included, for example, an anionic surfactant for making the monomer soluble or emulsified in a water-rich solvent may be included. As the anionic surfactant, an anionic surfactant that is stable in a water-rich solvent may be used without particular limitation. Representative anionic surfactants are shown below.
[0073] First, fatty acid salt type surfactants can be cited, such as sodium laurate, sodium palmitate and sodium stearate. Second, amino acid type surfactants can be cited, such as sodium lauroyl glutamate, sodium lauroyl aspartate and sodium lauroyl methylalanine. Third, sulfate type surfactants can be cited, such as alkyl sulfate ester salts such as sodium dodecyl sulfate and sodium myristyl sulfate, alkyl ether sulfate ester salts such as sodium polyoxyethylene lauryl ether sulfate and sodium polyoxyethylene alkyl ether sulfate. Second, sulfonic acid type surfactants can be cited, such as alkyl sulfonates such as sodium decyl sulfonate and sodium dodecyl sulfonate, alkyl benzene sulfonates such as sodium octylbenzene sulfonate and sodium dodecylbenzene sulfonate, alkyl naphthalene sulfonates such as sodium isopropylnaphthalene sulfonate and sodium butylnaphthalene sulfonate, polymer sulfonates such as sodium polystyrene sulfonate, olefin sulfonates such as sodium tetradecene sulfonate, and sulfonic fatty acid ester salts such as sodium dioctyl sulfosuccinate. In addition, alkyl phosphate-type surfactants such as sodium lauryl phosphate, sodium myristyl phosphate, and sodium polyoxyethylene lauryl phosphate can be mentioned.
[0074] The anionic surfactant may be used alone or in a mixture of two or more thereof in an amount sufficient to dissolve or emulsify the monomer. If the anionic surfactant is a sulfonic acid surfactant and / or a sulfate ester surfactant, it is preferred because it leads to a hybrid electrolytic capacitor having excellent frequency characteristics.
[0075] Electrolytic polymerization can be carried out by any method of constant potential method, constant current method and potential scanning method. In the case of constant potential method, although it depends on the type of monomer, the potential is preferably 1.0 to 1.5 V for saturated calomel electrode, and in the case of constant current method, although it depends on the type of monomer, it is preferably 1 to 10000 μA / cm 2 The current value, when using the potential scanning method, depends on the type of monomer, but it is suitable to scan the range of 0 to 1.5 V at a speed of 5 to 200 mV / sec for a saturated calomel electrode. The polymerization temperature is not strictly limited, but it is generally in the range of 10 to 60°C. The polymerization time is also not strictly limited, but it is generally in the range of 1 minute to 10 hours. The thickness of the organic conductive layer is generally in the range of 10 to 2000 nm, preferably in the range of 35 to 700 nm, and particularly preferably in the range of 70 to 350 nm.
[0076] The organic conductive layer after electrolytic polymerization is washed with water, ethanol or the like and dried to obtain a cathode for the hybrid electrolytic capacitor of the present invention.
[0077] (2) Anode Formation Process
[0078] In the anode forming process, a dielectric layer is formed by oxidizing the surface of an anode substrate formed of a valve metal. As the anode substrate, a substrate formed of a valve metal used as an anode substrate in a conventional solid electrolytic capacitor can be used without particular limitation. For example, a foil formed of valve metals such as aluminum, tantalum, niobium, titanium, hafnium, zirconium, zinc, tungsten, bismuth and antimony and having a surface area increased by applying a chemical or electrochemical etching treatment can be used, and aluminum foil is particularly preferred. The etch pits in the anode substrate can be tunnel pits, sponge pits, through-type pits, or residual core pits, which can be appropriately selected according to the purpose of the hybrid electrolytic capacitor. These etch pits can be formed using known alternating current electrolysis methods and direct current electrolysis methods. The dielectric layer on the surface of the anode substrate can be formed using a known method of applying a chemical treatment using a chemical solution such as an aqueous solution of ammonium borate, an aqueous solution of ammonium adipate, or an aqueous solution of ammonium phosphate to the anode substrate.
[0079] (3) Composite electrolyte layer formation step
[0080] The composite electrolyte layer forming step includes a step of filling a dispersion containing conductive polymer particles and a dispersion medium between the organic conductive layer of the cathode and the dielectric layer of the anode and drying the dispersion to form a solid electrolyte layer, and a step of impregnating the solid electrolyte layer with an electrolyte solution.
[0081] Typically, a spacer is disposed between the organic conductive layer of the cathode and the dielectric layer of the anode, and a solid electrolyte layer in contact with both the organic conductive layer of the cathode and the dielectric layer of the anode is maintained in the spacer. For example, the above-mentioned cathode and the above-mentioned anode in a strip shape can be stacked with the spacer so that the organic conductive layer of the cathode faces the dielectric layer of the anode, and then wound, thereby forming a capacitor element, and then a solid electrolyte layer is formed. In addition, the above-mentioned cathode and the above-mentioned anode in a desired shape can be stacked with the spacer so that the organic conductive layer of the cathode faces the dielectric layer of the anode, and then a solid electrolyte layer is formed after the capacitor element is formed. In addition, a solid electrolyte layer can be formed after forming a capacitor element in which multiple groups of cathodes and anodes are alternately stacked in a manner in which the organic conductive layer of the cathode faces the dielectric layer of the anode by sandwiching the spacer therebetween. As spacers, woven or non-woven fabrics formed from cellulose fibers, such as Manila paper, kraft paper, Spanish straw pulp paper, hemp paper, cotton paper, rayon and mixed papers thereof, woven or non-woven fabrics formed from polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate and their derivatives, polytetrafluoroethylene resins, polyvinylidene fluoride resins, vinylon resins, aliphatic polyamides, semi-aromatic polyamides, wholly aromatic polyamides and other polyamide resins, polyimide resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, acrylic resins, etc., cellophane, mixed papers of cellophane and Manila paper, kraft paper, etc. can be used.
[0082] The solid electrolyte layer is formed by filling a dispersion containing particles of a conductive polymer and a dispersion medium between the organic conductive layer of the cathode and the dielectric layer of the anode and drying the dispersion medium. As the dispersion medium, a dispersion medium that does not dissolve or substantially does not dissolve the particles of the conductive polymer contained in the dispersion is selected and used, and water can be particularly preferably used.
[0083] The preparation of the dispersion is obtained, for example, by the following operation, that is, adding monomers, an acid or its salt that releases dopants and an oxidant to water as a dispersion medium, stirring until the chemical oxidation polymerization is completed, and then, after removing the oxidant and residual monomers by purification methods such as ultrafiltration, cation exchange and anion exchange, ultrasonic dispersion treatment, high-speed fluid dispersion treatment, high-pressure dispersion treatment and other dispersion treatments are applied as needed. As a monomer, a monomer with a π-conjugated double bond given above for forming an organic conductive layer can be used, and a monomer selected from thiophene having a substituent at the 3rd and 4th positions can be preferably used. The substituents at the 3rd and 4th positions of the thiophene ring can form a ring together with the carbon at the 3rd and 4th positions. In particular, 3,4-(ethylenedioxythiophene) provides a conductive polymer that shows high conductivity and excellent heat resistance, so it is preferred. As an acid or its salt that releases a dopant, the compounds exemplified as supporting electrolytes above can be used, and compounds that release polyanions, especially polystyrene sulfonic acid or its salt can be appropriately used. As the oxidizing agent, trivalent iron salts such as iron (III) p-toluenesulfonate, iron (III) naphthalenesulfonate, and iron (III) anthraquinonesulfonate, or persulfates such as ammonium peroxodisulfate and sodium peroxodisulfate can be used.
[0084] In addition, it can be obtained by the following operation, that is, adding the above-mentioned monomer and the above-mentioned acid or salt of the dopant release agent to water as a dispersion medium, stirring and performing electrolytic oxidative polymerization, and then removing the residual monomer by purification methods such as ultrafiltration, cation exchange and anion exchange, and applying ultrasonic dispersion treatment, high-speed fluid dispersion treatment, high-pressure dispersion treatment and other dispersion treatments as needed. In addition, it can be obtained by the following operation, that is, filtering the liquid obtained by the above-mentioned chemical oxidative polymerization method or electrolytic polymerization method to separate the coagulant, adding it to water after sufficient washing, and applying ultrasonic dispersion treatment, high-speed fluid dispersion treatment, high-pressure dispersion treatment and other dispersion treatments. The content of the conductive polymer particles in the dispersion is generally in the range of 1.0 to 3.0 mass%, preferably in the range of 1.5 mass% to 2.0 mass%. The particle size of the conductive polymer in the dispersion is generally in the range of 10 to 1000nm. There is no strict restriction on the drying temperature, which is generally in the range of 50 to 200°C. There is no strict restriction on the drying time, which is generally in the range of 1 to 10 hours.
[0085] The conductive polymer in the organic conductive layer of the cathode and the conductive polymer in the solid electrolyte layer may be derived from the same monomer or different monomers. As shown above, the conductive polymer in the organic conductive layer is preferably poly(3,4-ethylenedioxythiophene). If the conductive polymer in the solid electrolyte layer is also poly(3,4-ethylenedioxythiophene), particularly high conductivity and high temperature durability can be obtained, so it is preferred.
[0086] Then, the obtained solid electrolyte layer is impregnated with an electrolyte solution under normal pressure or reduced pressure, thereby forming a composite electrolyte layer between the organic conductive layer of the cathode and the dielectric layer of the anode.
[0087] As the electrolyte, a known electrolyte containing at least a solvent and a solute dissolved therein can be used, and it can be appropriately selected according to the operating temperature and other requirements required for the hybrid electrolytic capacitor. As the electrolyte, for example, benzoate, butyrate, phthalate, isophthalate, terephthalate, salicylate, tartrate, oxalate, malonate, malate, valeric acid, ethyl acetate, ethyl acetate, methyl cellosolve, ethylene glycol monomethyl ether, cyclopentane, 3-methylcyclopentane, 2,4-dimethylcyclopentane, propylene carbonate, acetonitrile, water and the like can be used. The electrolyte obtained by using solutes such as diacid salt, adipate, azelaic acid salt, maleate, fumarate, citrate, pyromellitic acid salt, trimellitic acid salt, 1,6-decanedioate, formate, acetate, glycolate, lactate, 1-naphthoate, mandelate, citraconic acid, 2,4-dihydroxybenzoate, 2,5-dihydroxybenzoate, 2,6-dihydroxybenzoate, boron disalicylate, boron dioxalate, boron dimalonate. As salt, quaternary ammonium salts such as ammonium salt, tetramethylammonium salt, triethylmethylammonium salt, quaternary amidinium salts such as ethyldimethylimidazolium salt, tetramethylimidazolium salt, trimethylamine salt, triethylamine salt can be illustrated. The above-mentioned solvent can be used alone or in combination of two or more. The above-mentioned solute can also be used alone or in combination of two or more. These electrolytes may contain, in addition to the above-mentioned solvents and solutes, known additives. For example, in order to improve the voltage resistance of the capacitor, phosphoric acid, phosphate compounds such as phosphoric acid and phosphate esters, boric acid compounds such as boric acid, sugar alcohols such as mannitol, complexes of boric acid and sugar alcohols, polyoxyalkylene polyols such as polyethylene glycol, polyglycerol, and polypropylene glycol may be contained. In addition, in particular, nitro compounds such as nitrophenol, nitrobenzoic acid, nitroanisole, and nitrobenzyl alcohol may be contained for the purpose of absorbing hydrogen generated violently at high temperatures.
[0088] Then, the capacitor element with the composite electrolyte layer added is placed in an outer packaging box and sealed to obtain the hybrid electrolytic capacitor of the present invention. In the hybrid electrolytic capacitor of the present invention, as described above, since the organic conductive layer containing the conductive polymer in the cathode is in contact with the composite electrolyte layer, it can also bring high electrostatic capacitance, low ESR, excellent high-frequency characteristics and high high-temperature durability.
[0089] Example
[0090] The present invention will be described below using the following examples; however, the present invention is not limited to the following examples.
[0091] Example 1
[0092] As a cathode substrate for obtaining a cathode, an aluminum foil with sponge-like etch pits was used. The aluminum foil was subjected to a chemical treatment using an aqueous solution of ammonium dihydrogen phosphate as a chemical treatment solution, and a chemical treatment voltage of 5.0 V was formed on the surface of the aluminum foil. fs Then, a vapor-deposited film containing titanium carbide is formed on the surface of the chemically formed oxide film by arc ion plating, thereby obtaining a support having a vapor-deposited titanium carbide film (inorganic conductive layer).
[0093] 50 mL of distilled water was introduced into a glass container and heated to 40°C. 0.021 M of 3,4-(ethylenedioxythiophene) (hereinafter, 3,4-(ethylenedioxythiophene) is referred to as "EDOT" and poly(3,4-(ethylenedioxythiophene)) is referred to as PEDOT) and 0.08 M of ammonium borodisalicylate were added to the liquid and stirred to obtain a polymerization solution for electrolytic polymerization. Then, the support (working electrode) and a 10 cm 2 The area of the SUS mesh is used as the counter electrode at 0.1 mA / cm 2 The working electrode after polymerization was washed with water and dried at 100°C for 30 minutes to form a 35nm thick and about 1.6g / cm 3 The thickness of the PEDOT layer is a value obtained by performing a 0.1 mA / cm2 test multiple times at different times. 2 The constant current electropolymerization is carried out under conditions of , and the thickness of the PEDOT layer obtained in each experiment is measured using an atomic force microscope or a step difference detector. After deriving a relationship between the thickness of the PEDOT layer and the amount of charge, the derived relationship is used to convert the amount of charge of the electropolymerization into the thickness of the PEDOT layer.
[0094] As the anode substrate for obtaining the anode, an etched aluminum foil was used. The aluminum foil was subjected to a chemical conversion treatment using an aqueous solution of ammonium adipate as a chemical conversion solution, and a chemical conversion voltage of 47.3 V was formed on the surface of the aluminum foil. fs An oxide film (dielectric layer) is formed to obtain an anode for a hybrid electrolytic capacitor.
[0095] The obtained anode and cathode were connected to terminals, and the dielectric layer of the anode and the organic conductive layer of the cathode were stacked and wound with a separator interposed therebetween. Then, the anode was repaired and formed for 15 minutes using an aqueous solution of ammonium dihydrogen phosphate under the conditions of an applied voltage of 40.5 V and 10 mA, and then dried at 105° C. for 30 minutes to obtain a capacitor element.
[0096] The microparticles of poly(3,4-ethylenedioxythiophene) and polystyrene sulfonic acid were dispersed in a dispersion medium obtained by adding 5% by mass of ethylene glycol to water to obtain a dispersion liquid for forming a solid electrolyte layer. The obtained dispersion liquid was impregnated into the above capacitor element at a pressure of 30 kPa for 120 seconds and dried at 150° C. for 30 minutes. The dispersion liquid impregnation and drying were repeated again to obtain a capacitor element with an additional solid electrolyte layer.
[0097] An electrolyte solution in which 5% by mass of ammonium borodisalicylate was dissolved in ethylene glycol was prepared. The electrolyte solution was quantitatively sprayed onto a capacitor element to which a solid electrolyte layer was added, thereby allowing the electrolyte solution to penetrate into the solid electrolyte layer, thereby obtaining a capacitor element to which a composite electrolyte layer was added. The obtained element was sealed in an outer packaging box to obtain a hybrid electrolytic capacitor with a diameter of 8 mm and a height of 10 mm.
[0098] The obtained hybrid electrolytic capacitor was aged for 45 minutes at 115°C while applying a voltage of 28.2V to the capacitor to obtain a hybrid electrolytic capacitor with a rated voltage of 25V. As the initial characteristics of the obtained capacitor, the electrostatic capacitance at 120Hz and 20kHz and the ESR at 20kHz and 100kHz were measured at 20°C. Then, as a durability test, a high-temperature durability test was performed at a high temperature of 150°C with a DC voltage of 25V applied for 4000 hours. As the characteristics after the durability test, the electrostatic capacitance at 120Hz and 20kHz and the ESR at 20kHz and 100kHz were measured again at 20°C.
[0099] Example 2
[0100] The electrolytic polymerization solution used in Example 1 was used at 0.1 mA / cm 2 The constant current electrolytic polymerization was carried out for 2 minutes under the conditions of , thereby obtaining a cathode having a PEDOT layer (organic conductive layer) on the titanium carbide vapor-deposited film (inorganic conductive layer), wherein the PEDOT layer has a thickness of 70 nm and has a carbon content of about 1.6 g / cm 3 The procedure of Example 1 was repeated except for this point.
[0101] Example 3
[0102] The electrolytic polymerization solution used in Example 1 was used at 0.1 mA / cm 2 The constant current electrolytic polymerization was carried out for 4.5 minutes under the conditions of , thereby obtaining a cathode having a PEDOT layer (organic conductive layer) on the titanium carbide vapor-deposited film (inorganic conductive layer), wherein the PEDOT layer has a thickness of 150 nm and has a carbon content of about 1.6 g / cm 3 The procedure of Example 1 was repeated except for this point.
[0103] Example 4
[0104] The electrolytic polymerization solution used in Example 1 was used at 0.1 mA / cm 2 The constant current electrolytic polymerization was carried out for 10 minutes under the conditions of , thereby obtaining a cathode having a PEDOT layer (organic conductive layer) on the titanium carbide vapor-deposited film (inorganic conductive layer), wherein the PEDOT layer has a thickness of 350 nm and has a carbon content of about 1.6 g / cm 3 The procedure of Example 1 was repeated except for this point.
[0105] Comparative Example 1
[0106] Aluminum foil with sponge-like pits was used as a cathode substrate for obtaining a cathode. The aluminum foil was subjected to a chemical treatment using an aqueous solution of ammonium dihydrogen phosphate as a chemical treatment solution, and a chemical treatment voltage of 3.0 V was formed on the surface of the aluminum foil. fs The procedure of Example 1 was repeated except that the obtained cathode was used instead of the cathode of Example 1.
[0107] Comparative Example 2
[0108] Aluminum foil with sponge-like pits was used as a cathode substrate for obtaining a cathode. The aluminum foil was subjected to a chemical treatment using an aqueous solution of ammonium dihydrogen phosphate as a chemical treatment solution, and a chemical treatment voltage of 5.0 V was formed on the surface of the aluminum foil. fs Then, a vapor-deposited film containing titanium carbide is formed on the surface of the chemically formed oxide film by arc ion plating, thereby obtaining a cathode having a vapor-deposited titanium carbide film (inorganic conductive layer) and no organic conductive layer. The steps of Example 1 were repeated except that the obtained cathode was used instead of the cathode of Example 1.
[0109] Example 5
[0110] An aluminum foil without etch pits is used as a cathode substrate for obtaining a cathode. In this example, a natural oxide film is used as an oxide layer instead of a chemically formed oxide film. Then, instead of forming a titanium carbide vapor-deposited film, a vapor-deposited film containing carbon is formed on the surface of the natural oxide film by sputtering to obtain a support having a carbon vapor-deposited film (inorganic conductive layer).
[0111] The above-mentioned support and a 10 cm 2 The area of the SUS mesh is used as the counter electrode at 0.1 mA / cm 2 The working electrode after polymerization was washed with water and dried at 100°C for 30 minutes to form a 350nm thick and about 1.6g / cm 3 A PEDOT layer (organic conductive layer) having a density of 1000 Å was formed to obtain a cathode for a hybrid electrolytic capacitor. The procedure of Example 1 was repeated except that the obtained cathode was used instead of the cathode of Example 1.
[0112] Comparative Example 3
[0113] An aluminum foil without etch pits is used as a cathode substrate for obtaining a cathode. In this example, a natural oxide film is used as an oxide layer instead of a chemically formed oxide film. Then, instead of forming a titanium carbide vapor-deposited film, a vapor-deposited film containing carbon is formed on the surface of the natural oxide film by sputtering, thereby obtaining a cathode having a carbon vapor-deposited film (inorganic conductive layer) and no organic conductive layer. The steps of Example 1 are repeated except that the obtained cathode is used instead of the cathode of Example 1.
[0114] Example 6
[0115] Aluminum foil with sponge-like pits was used as a cathode substrate for obtaining a cathode. The aluminum foil was subjected to a chemical conversion treatment using an aqueous solution of ammonium dihydrogen phosphate as a chemical conversion solution, and a chemical conversion voltage of 1.2 V was formed on the surface of the aluminum foil. fs The formed oxide film (oxide layer) is formed.
[0116] As carbon particles, flake graphite having an average particle size of 4.5 μm and acetylene black having an average primary particle diameter of 50 nm and an average secondary particle diameter of 0.3 μm were used, which were mixed in a mass ratio of 75:25, and the resulting mixture, styrene butadiene rubber, and an aqueous solution of sodium carboxymethyl cellulose were mixed in a mass ratio of 84:10:6 and dispersed using a stirrer to prepare a carbon slurry.
[0117] The obtained carbon slurry was applied onto the above-mentioned chemical oxide film and dried to form a slurry layer. The slurry layer was subjected to a linear pressure of 5.38 kNcm-1 The roller pressing was applied with a pressing process to obtain a support body for a hybrid electrolytic capacitor having a carbon coating film (inorganic conductive layer) with a thickness of 1 μm. The cross-section of the support body was observed using an SEM photograph, and as a result, acetylene black entered to a position of about 1 / 3 of the length of the etch pit. In addition, the flaky graphites were oriented so that their basal surfaces overlapped with each other, and acetylene black was filled between the graphites. Subsequently, the above-mentioned carbon slurry was applied to the carbon coating film of the support body for the hybrid electrolytic capacitor and dried, thereby preparing a support body for confirmation having a carbon coating film with a thickness of 20 μm. The interface resistance of the support body was measured using an electrode resistance measurement system (manufactured by Hioki Electric Chemical Co., Ltd., model RM2610), and the result was 1.78 mΩcm 2 , and the value is used to judge whether the carbon coating film of the support body for the hybrid electrolytic capacitor and the aluminum of the cathode substrate are conductive.
[0118] The above-mentioned support and a 10 cm 2 The area of the SUS mesh is used as the counter electrode at 0.1 mA / cm 2 The working electrode after polymerization was washed with water and dried at 100°C for 30 minutes to form a 350nm thick and about 1.6g / cm 3 A PEDOT layer (organic conductive layer) having a density of 1000 Å was formed to obtain a cathode for a hybrid electrolytic capacitor. The procedure of Example 1 was repeated except that the obtained cathode was used instead of the cathode of Example 1.
[0119] Comparative Example 4
[0120] Aluminum foil with sponge-like pits was used as a cathode substrate for obtaining a cathode. The aluminum foil was subjected to a chemical conversion treatment using an aqueous solution of ammonium dihydrogen phosphate as a chemical conversion solution, and a chemical conversion voltage of 1.2 V was formed on the surface of the aluminum foil. fs Then, a carbon coating film was formed by the same procedure as in Example 6 to obtain a cathode having a carbon coating film (inorganic conductive layer) and no organic conductive layer. The procedure of Example 1 was repeated except that the obtained cathode was used instead of the cathode of Example 1.
[0121] Table 1 shows the capacitance values at 20° C. obtained for the hybrid electrolytic capacitors of Examples 1 to 6 and Comparative Examples 1 to 4, and Table 2 shows the ESR values at 20° C. obtained for the hybrid electrolytic capacitors of Examples 1 to 6 and Comparative Examples 1 to 4.
[0122] [Table 1]
[0123]
[0124] [Table 2]
[0125]
[0126] First, the electrostatic capacitance of the hybrid electrolytic capacitor shown in Table 1 is studied. The practice of increasing the capacitance of the capacitor by making the cathode capacitance close to infinity using an inorganic conductive layer has been given in patent documents 3 to 7, but the previous evaluation was mainly carried out only under the condition of 120Hz, and no electrostatic capacitance in the high-frequency region (20kHz) was given. In addition, by comparing the capacitance of the capacitor with a cathode having a titanium carbide vapor-deposited film in Comparative Example 2 and the capacitor with a cathode having a carbon vapor-deposited film in Comparative Example 3 with the capacitance of the capacitor with a cathode having no inorganic conductive layer in Comparative Example 1, it can be found that the capacitance at 120Hz is indeed increased using the countermeasures of the existing literature, but the electrostatic capacitance in the high-frequency region (20kHz) is not increased. In contrast, the capacitance of the capacitor with a cathode having a carbon-coated film disclosed by the applicant in PCT / JP2019 / 022741 also increases in the high-frequency region (20kHz). This is because the carbon-coated film has an entry portion that enters the etch pit and a penetration portion that penetrates the oxide layer and is conductive to the cathode substrate.
[0127] In contrast, by comparing the capacitance of the capacitors of Examples 1 to 4 having a cathode with a dense organic conductive layer containing a conductive polymer with the capacitance of the corresponding capacitor of Comparative Example 2, comparing the capacitance of the capacitor of Example 5 with the capacitance of the corresponding capacitor of Comparative Example 3, and comparing the capacitance of the capacitor of Example 6 with the capacitance of the corresponding capacitor of Comparative Example 4, it can be clearly understood that the capacitance of the capacitors of the embodiments does not depend on the type of the inorganic conductive layer of the cathode, does not depend on whether the oxide layer is a chemically formed oxide film or a natural oxide film, and does not depend on the presence or absence of etching pits on the cathode substrate. Not only does the capacitance at 120 Hz increase, but the electrostatic capacitance at 20 kHz also increases. This is because a dense organic conductive layer containing a conductive polymer is provided at the cathode, so that the interface resistance between the organic conductive layer and the composite electrolyte layer can be reduced, which can be achieved as Figure 3 As shown in the left figure, the cathode oxide film resistor R COX Significantly greater than the interface resistance R IN The area is widened to the high frequency area.
[0128] In addition, it can be understood from Table 1 that for the capacitors of Examples 1 to 6, the change in electrostatic capacitance before and after the extremely severe high-temperature durability test at 150°C for 4000 hours is small in both the low-frequency region and the high-frequency region. The change in electrostatic capacitance before and after the high-temperature durability test is further improved in the capacitor using a cathode formed of an inorganic conductive layer made of carbon, compared with the capacitor using a cathode formed of titanium carbide, and in particular, the capacitor of Example 6 having a cathode with a carbon coating film shows excellent high-temperature durability.
[0129] Then, the ESR of the hybrid electrolytic capacitor shown in Table 2 was studied. By comparing the ESR of the capacitor with a cathode having a titanium carbide vapor-deposited film in Comparative Example 2 and the capacitor with a cathode having a carbon vapor-deposited film in Comparative Example 3 with the ESR of the capacitor with a cathode having no inorganic conductive layer in Comparative Example 1, it can be found that the use of the inorganic conductive layer of the existing literature not only increases the ESR at 20kHz, but also increases the ESR at 100kHz, and the change in ESR before and after the high-temperature endurance test becomes larger. In the capacitor of Comparative Example 4, it was also confirmed that the change in ESR before and after the high-temperature endurance test increased due to the use of the cathode having an inorganic conductive layer but not an organic conductive layer.
[0130] However, by comparing the ESR of the capacitors of Examples 1 to 4 having a cathode with a dense organic conductive layer containing a conductive polymer with the ESR of the corresponding capacitor of Comparative Example 2, comparing the ESR of the capacitor of Example 5 with the ESR of the corresponding capacitor of Comparative Example 3, and comparing the ESR of the capacitor of Example 6 with the ESR of the corresponding capacitor of Comparative Example 4, it can be clearly understood that the ESR of the capacitors of the examples does not depend on the type of the inorganic conductive layer of the cathode, and does not depend on whether the oxide layer is a chemically formed film or a natural oxide film, and does not depend on the presence or absence of etching pits on the cathode substrate, and not only the ESR at 20kHz is significantly reduced, but also the ESR at 100kHz is significantly reduced, and the change of ESR before and after the high-temperature endurance test is also significantly suppressed. This is because the dense organic conductive layer with excellent adhesion to both the composite electrolyte layer and the inorganic conductive layer is provided on the cathode, so the interface resistance is reduced, and the reduction of the interface resistance is also maintained in the high-temperature endurance test.
[0131] Industrial Applicability
[0132] According to the present invention, a hybrid electrolytic capacitor having high electrostatic capacitance, low ESR, excellent high-frequency characteristics, and high high-temperature durability can be obtained.
[0133] Description of Reference Numerals
[0134] 1 hybrid electrolytic capacitor, 10 cathode, 11 cathode substrate, 12 oxide layer, 13 inorganic conductive layer, 14 organic conductive layer, 20 anode, 21 anode substrate, 22 dielectric layer, 30 composite electrolyte layer, 31 solid electrolyte layer, 31a conductive polymer particles, 32 electrolyte solution.
Claims
1. A hybrid electrolytic capacitor, characterized in that: have: A cathode having a cathode substrate formed of a valve metal, an oxide layer formed of an oxide of the valve metal provided on a surface of the cathode substrate, an inorganic conductive layer comprising an inorganic conductive material provided on a surface of the oxide layer, and an organic conductive layer comprising a conductive polymer provided on a surface of the inorganic conductive layer; an anode including an anode substrate formed of a valve metal and a dielectric layer formed of an oxide of the valve metal constituting the anode substrate and provided on a surface of the anode substrate; as well as The composite electrolyte layer comprises a solid electrolyte layer containing conductive polymer particles provided between and in contact with the organic conductive layer of the cathode and the dielectric layer of the anode, and an electrolyte solution filled between the conductive polymer particles of the solid electrolyte layer.
2. The hybrid electrolytic capacitor according to claim 1, wherein: The organic conductive layer of the cathode has a thickness of 1.15 g / cm 3 ~1.80g / cm 3 The density of the range.
3. The hybrid electrolytic capacitor according to claim 1 or 2, wherein: The organic conductive layer of the cathode is an electrolytic polymer film.
4. The hybrid electrolytic capacitor according to claim 1 or 2, wherein: The conductive polymer in the organic conductive layer of the cathode and the solid electrolyte layer of the composite electrolyte layer is poly(3,4-ethylenedioxythiophene).
5. The hybrid electrolytic capacitor according to claim 1 or 2, wherein: The inorganic conductive material constituting the inorganic conductive layer is carbon.
6. The hybrid electrolytic capacitor according to claim 1 or 2, wherein: The cathode substrate has etch pits, The inorganic conductive layer is a carbon coating layer containing carbon particles, The carbon coating layer includes an entry portion that enters the etch pit and a penetration portion that penetrates the oxide layer and is in conduction with the cathode substrate.
7. A method for manufacturing a hybrid electrolytic capacitor, characterized in that: include: A cathode forming step, comprising a step of forming an inorganic conductive layer using an inorganic conductive material on a surface of an oxide layer formed of an oxide of a valve metal provided on a surface of a cathode substrate formed of a valve metal, and a step of forming an organic conductive layer including a conductive polymer on the surface of the inorganic conductive layer by electrolytic polymerization of a monomer having a π-conjugated double bond; an anode forming step of forming a dielectric layer by oxidizing a surface of an anode substrate formed of a valve metal; as well as The composite electrolyte layer forming step includes a step of filling a dispersion containing conductive polymer particles and a dispersion medium between the organic conductive layer of the cathode and the dielectric layer of the anode and drying the dispersion to form a solid electrolyte layer, and a step of impregnating the solid electrolyte layer with an electrolyte solution.
8. The method for manufacturing a hybrid electrolytic capacitor according to claim 7, wherein: The density of the organic conductive layer is 1.15 g / cm 3 ~1.80g / cm 3 range.
Citation Information
Patent Citations
Solid electrolytic capacitor and its manufacture
JP2000114109A
Solid electrolytic capacitor
JP2005109270A
Electrolyte capacitor and manufacturing method thereof
JP2006190878A
Aluminum cathode foil for electrolytic capacitor and manufacturing method thereof
JP2007095865A
Electrolytic-capacitor and manufacturing method therefor
JP2008010657A